The art of murder : a dead-end job mystery - Viets, Elaine, 1950- (Viets, Elaine,2016001087 1950- Dead-end job mystery series., 2016)
"From the national bestselling author of Checked Out, PI Helen Hawthorne must pose as a painter at Fort Lauderdale's famous Bonnet House Museum to catch an artful killer.... The art world is a happening place--but a brush with death shouldn't be in the picture. Unfortunately, that's just what happens to Helen Hawthorne and her friend Margery. While touring gorgeous Bonnet House, a mansion turned museum, they observe a painting class and note an up-and-coming artist. When they later see her deadly end, Helen is hired to canvas the crime scene--undercover, of course. Sketchy suspects lurk in the victim's bohemian past. Was the promising painter killed by her jealous husband? Her best friend? A rival using her artful wiles? With her husband, Phil, busy setting a trap for a gold thief, it's up to Helen to paint this killer into a corner..."--